The acquisition of the English article system : the case of Malaysian secondary school students - Beena Sudhakaran
The purpose of this study is to determine how English as a Foreign Language (EFL) students acquire the English article system. The subjects were Advanced Level students (Grade 12) from Tsun Jin High School, in Kuala Lumpur, Malaysia, where English is taught as a second language. This was a case study where seven students were randomly selected for this research. As the subjects' use of the English article system would be clearly maniifested through their language productive skills, it was decided that their performance in writing and speaking be studied. Therefore their journal entries and essays were examined. Secondly, interviews were conducted with the subjects, both in the school and playh environments, and finally students were asked to make oral presentations on topics of their choice. The interviews and oral presentations were recorded and subsequently transcribed so as to allow easier analysis of the students' article use in these oral tasks. From the analysis of data it was found that with respect to acquision of the articles, 'the' was acqird first, followed by 'a' and finally the zero article. With respect to overgeneralisation it was found that students tend to overgeneralise the use of article 'the' rather than the article 'as'. In addition, students had a higher degree of accuracy in writing than in speaking. Most importantly, it was found that the subjects had not acquired the article system naturally. The findings of this study have some pedagogical implications. Teachers need to be aware that the article system iis among the most difficult of the grammatical systems; such a system may not be naturally acquired. This warrants a pedagogical approach that helps learners to raise their language awareness. Among other things, teachers should realize the order in which articles are acquired, so as to to be able to plan appropriate teaching strategies.